KESESUAIAN ANAMNESE KEFARMASIAN OLEH APOTEKER TERHADAP DIAGNOSIS DOKTER DI APOTEK DI WILAYAH KABUPATEN GIANYAR - Mynarti, Sari; Noviyani, Rini; Dewi, Luh Putu Mirah Kusuma (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2015)
A study of pharmaceutical anamneses relevance by pharmacist compared to doctors’ diagnose in 5 pharmacies in Gianyar had been done. The study was descriptive retrospective using 400 prescriptions that come into pharmacies during three months periods, from April to June 2009. The aims of this study was to figure out the relevance between pharmaceutical anamneses that had been done by the pharmacist compared to doctors’ diagnose based on clinical symptoms of disease and medical terminology, and also to know the length of time which was needed to do pharmaceutical anamneses on single prescription. From 400 prescriptions that were used in this study, 80.75% showed the relevance between pharmaceutical anamneses compared to doctors’ diagnose and 19.25% showed the irrelevance according to clinical symptom of disesases. Meanwhile, according to medical terminology that had been used, the relevance level between the pharmaceutical anamneses by pharmacist compared to doctors’ diagnose are 22% and 78% showed the irrelevance.The average time used by pharmacist to do pharmaceutical anamnese of single prescription was 6.49 seconds.